Animal Models of Schizophrenia and Related Disorders - O'Donnell, Patricio.; O'Donnell, Patricio. (Neuromethods, 2011)
Animal models of schizophrenia and other major psychiatric disorders have been sought for decades, and, as a result, we are now facing new vistas on pathophysiology that could lead to novel therapeutic approaches and even hint at possible preventive strategies. Animal Models of Schizophrenia and Related Disorders presents an overview of the information that can be obtained with several different models and a detailed account of how to generate such models in order to ensure that the manipulations used to model schizophrenia-relevant phenomena are used consistently across laboratories.  This detailed volume features pharmacological models such as non-competing NMDA antagonists, emphasizing their use in vitro, neurodevelopmental models such as the neonatal ventral hippocampal lesion and the antimitotic MAM, models that reproduce environmental factors such as neonatal hypoxia, vitamin D deficits, and prenatal immune activation, as well as several different genetic model approaches.  As a volume in the Neuromethods series, this volume contains the kind of detailed description and implementation advice that is crucial for getting optimal results.   Practical and cutting-edge, Animal Models of Schizophrenia and Related Disorders highlights the successes in the use of animal models to gain insight on pathophysiological mechanisms of relevance to major psychiatric disorders in the hope of inspiring investigators to expand the research and test targets that could restore or ameliorate function.